Outcome of breech delivery: caesarean section versus vaginal delivery at Patan Hospital, Patan Academy of Health Sciences (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Obstetricians have long debated the role of caesarean section as a potentially safer mode of delivery for the fetus with breech presentation. However, the experience of the health care provider remains a critical element in the decision to pursue a vaginal breech delivery, and it may still be a viable option. The aim of this study is to determine the incidence of breech delivery at Patan Hospital and compare maternal and neonatal outcomes subjected to either vaginal or caesarean section.Methods: This was a five-year retrospective study of breech deliveries covering the year 2010 to 2014. Patient’s charts were retrieved from the medical record section and reviewed.Results: There were 896 breech deliveries out of a total 44,842 deliveries giving an incidence of 1.99%. One hundred thirteen (12.61%) of breech deliveries were through vaginal route while 431 (48.10%) and 352 (39.28%) were through emergency and elective caesarean sections respectively. There were 154 (17.18%) preterm breech deliveries including 27 (17.5%) preterm intrauterine death. Among term pregnancy, there were 3 neonatal deaths not associated with mode of delivery. None of the term infant had neurological morbidity comprising neonatal seizures, brachial plexus injury, chephalohematoma. Maternal blood loss was significantly higher in caesarean section group. Conclusions: In well-selected cases, the neonatal outcome following assisted vaginal breech delivery and caesarean section may not be different.Journal of Patan Academy of Health Sciences, Vol. 3, No. 1, 2016. page: 4-9